2021
DOI: 10.1136/bjsports-2020-103833
|View full text |Cite
|
Sign up to set email alerts
|

Lower step rate is associated with a higher risk of bone stress injury: a prospective study of collegiate cross country runners

Abstract: ObjectivesTo determine if running biomechanics and bone mineral density (BMD) were independently associated with bone stress injury (BSI) in a cohort of National Collegiate Athletic Association Division I cross country runners.MethodsThis was a prospective, observational study of 54 healthy collegiate cross country runners over three consecutive seasons. Whole body kinematics, ground reaction forces (GRFs) and BMD measures were collected during the preseason over 3 years via motion capture on an instrumented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 40 publications
0
28
1
Order By: Relevance
“…It is worth noting for the average slope from 20% to 80% of the vGRF magnitude at IP method that methodological discrepancies exist with some studies calculating LR using the region between 20% and 80% of the vGRF magnitude at IP (8,26,27) and others using the region between 20% and 80% of the time to IP (4,7,10). These methods are not interchangeable, and due to unclear verbiage, it is at times difficult to determine which calculation method was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting for the average slope from 20% to 80% of the vGRF magnitude at IP method that methodological discrepancies exist with some studies calculating LR using the region between 20% and 80% of the vGRF magnitude at IP (8,26,27) and others using the region between 20% and 80% of the time to IP (4,7,10). These methods are not interchangeable, and due to unclear verbiage, it is at times difficult to determine which calculation method was used.…”
Section: Discussionmentioning
confidence: 99%
“…Despite vGRF being only one of the many forces contributing to the complex internal loading patterns associated with injury, LR is often used as a simplified measure of this loading. However, the role of LR in running-related injuries is unclear, with some studies demonstrating an association between high LR and injury (1-3), particularly bone stress injuries (BSI) (4)(5)(6), and others finding no relationship (7)(8)(9)(10). Inconsistent findings regarding the association of LR and injury may be related to the varying methods used to calculate LR, data collections occurring at different running speeds, and study design limitations.…”
mentioning
confidence: 99%
“…A recent trial found that healthy adolescent runners did not modify their footstrike pattern after 10-week running retraining programs designed to promote a transition to a non-rearfoot strike (González et al, 2021), suggesting unique approaches may be necessary in this population. Nonetheless, given the increased risk of shin pain in high school runners and of BSI in collegiate runners using a lower step rate (Luedke et al, 2016;Kliethermes et al, 2021), running retraining in this population may be considered as part of a comprehensive treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…The vertical loading rate (VLR), defined as the rate of change of the force application after the impact, has been used as the best indicator to describe ground impact [7]. Additionally, common pathologies in runners (i.e., patellofemoral syndrome, tibial stress fracture, and plantar fasciitis) have been linked to VLR [8], although recent studies reported no relationship between VLR and injury risk in level running [9,10], contrary to lower step rate [11] or lower duty factor [9]. However, downhill running elicits very greater VLR values than in level running and a lower step rate at the same speed as in uphill running [12].…”
Section: Open Accessmentioning
confidence: 99%